Efektivitas Dosis Plant Growth Promoting Rhizobacteria (PGPR) Akar Bambu Terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris L.) - Andi Mariani; Nani Rohaeni (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Nani Rohaeni SP.,MP and Ir. Andi Mariani Z, MP. The effect of giving Plant Growth Promoting Rhizobacteria (PGPR) bamboo root on the growth and yield green beans (Paseolus vulgaris L.). The purpose of this research to know the effect of gifting Plant Growth Promoting Rhizobacteria (PGPR) to growth and results bean plants (Paseolus vulgaris L.). This research held in months december 2021 to february 2022, located at Tebangan Lemba street, Sepaso Barat village, Bengalon subdistrict, Kutai Timur Regency. Methods used by randomized design (RAK) faktorial witch the treatment factor, the PGPR administration factor of the five treatmen levels are: (P0) without teratment, (P1) 5 ml/L, (P2) 7,5 ml/L, (P3) 10 ml/L, and 12,5 ml/L. Combined as many as five treatman combinations and at times five groups. The results of this study indicate that the P4 treatmen (PGPR 12,5 ml/L) produce the larges fruit weight 418,6 grams and production of 20,93 tons/ha.